Ultra violet escape fractions from giant molecular clouds during early cluster formation - Howard, Corey S.; Pudritz, Ralph E.; Klessen, Ralf S. (Arxiv, 2017)
The UV photon escape fraction from molecular clouds is a key parameter for understanding the ionization of the Interstellar Medium (ISM), and extragalactic processes, such as cosmic reionization. We present the ionizing photon flux and the corresponding photon escape fraction (f$_{esc}$) arising as a consequence of star cluster formation in a turbulent, 10$^6$ M$_{\odot}$ GMC, simulated using the code FLASH. We make use of sink particles to represent young, star-forming clusters coupled with a radiative transfer scheme to calculate the emergent UV flux. We find that the ionizing photon flux across the cloud boundary is highly variable in time and space due to the turbulent nature of the intervening gas. The escaping photon fraction remains at $\sim$5% for the first 2.5 Myr, followed by two pronounced peaks at 3.25 and 3.8 Myr with a maximum f$_{esc}$ of 30% and 37%, respectively. These peaks are due to the formation of large HII regions, that expand into regions of lower density and some of which reach the cloud surface. However, these phases are short lived and f$_{esc}$ drops sharply as the HII regions are quenched by the central cluster passing through high-density material due to the turbulent nature of the cloud. We find an average f$_{esc}$ of 15% with factor of two variations over 1 Myr timescales. Our results suggest that assuming a single value for f$_{esc}$ from a molecular cloud is in general a poor approximation, and that the dynamical evolution of the system leads to large temporal variation.